Solid-phase synthesis of homodetic cyclic peptides from Fmoc-MeDbz-resin. Issue 18 (2nd May 2018) - Abdel Monaim, Shimaa A.H.; Acosta, Gerardo A.; Royo, Miriam; El-Faham, Ayman; de la Torre, Beatriz G.; Albericio, Fernando
Graphical abstract: Highlights: Efficient solid-phase synthesis of homodetic cyclic peptides. MeDbz linker as a safety catch linker. High purity of final cyclic peptides thanks to the cyclative cleavage. Abstract: Cyclic homodetic peptides are very appealing for medicinal chemistry programs. In addition to the high efficiency and selectivity inherently associated with peptides, a cyclic structure totally formed by amide bonds increases their stability under physiological conditions. Here Fmoc-MeDbz-resin was studied for the preparation of these peptides. Our results demonstrate the usefulness of this strategy for the preparation of cyclic "head-to-side chain" peptides through cyclative cleavage (simultaneous cyclization and release from the resin). In contrast, for the synthesis of the "head-to-tail" counterparts, the cyclization-cleavage should be carried out in the presence of thiophenol.